Tools for screening maternal mental health conditions in primary care settings in sub-Saharan Africa: systematic review - Gyimah, Leveana; Agyepong, Irene Akua; Owiredu, David; Awini, Elizabeth; Yevoo, Linda Lucy; Ashinyo, Mary Eyram; Aye, Sorre Grace Emmanuelle Victoire; Abbas, Shazra; Cronin de Chavez, Anna; Mirzoev, Tolib; Danso-Appiah, Anthony (Frontiers in Public Health, 2024)
Introduction In sub-Saharan Africa, pregnant and postpartum women with mental health problems are often missed in healthcare systems. To address this, a practical and simple screening tool for maternal mental health should be available to primary healthcare workers. An important step toward having such a tool is to assess the existing tools and their effectiveness in primary care settings. Methods We systematically searched PubMed, LILAC, CINAHL, Google Scholar, African Index Medicus, HINARI, and African Journals Online from inception to 31 January 2023, without language restriction. Reference lists of retrieved articles were reviewed and experts in the field were contacted for studies not captured by our searches. All retrieved records were collated in Endnote, de-duplicated, and exported to Rayyan for screening. Study selection and data extraction were done by at least two reviewers using a pre-tested flow chart and data extraction form. Disagreements between reviewers were resolved through discussion. We contacted primary authors for missing or insufficient information and conducted a content analysis of the psychometric properties of the tools. Results In total, 1,181 studies were retrieved by our searches, of which 119 studies were included in this review. A total of 74 out of 119 studies (62%) were screened for depression during pregnancy and or the postpartum period. The Edinburg Postpartum Depression Scale (EPDS) and the Patient Health Questionnaire (PHQ-9) were the most commonly used tools. In total, 12 studies reported specificity and sensitivity for tools for measuring depression (EPDS, PHQ-9, and Whooley) and psychological distress [Self Report Questionnaire (SRQ) and Kessler Psychological Distress Scale (KPDS)]. The average sensitivity and specificity of the EPDS reported were 75.5 and 76.5%, respectively, at a cut-off of ≥13. The EPDS appears to be the most acceptable, adaptable, user-friendly, and effective in screening for maternal mental health conditions during pregnancy and postpartum. However, the methodological approach varied for a particular tool, and documentation on the attributes was scanty. Conclusion The EPDS was the most commonly used tool and considered as most acceptable, adaptable, user-friendly, and effective. Information on the performance and psychometric properties of the vast majority of screening tools was limited. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022323558, identifier CRD42022323558 (PROSPERO).